PENERAPAN METODE DISCOVERY LEARNING BERBASIS ICT PADA PEMBELAJARAN TEKS EKSPOSISI KELAS X DI SMAN 1 NGAMPRAH - Windy Wulandari Rahayu; Via Nugraha; Reka Yuda Mahardika (IKIP Siliwangi, 2023)
In the 21st century, it encorages teachers and students to be able to keep up with the times. The 4C skills needed in the 21st century include critical thinking, communication, creative thinking, and collaboration. Process of learning Indonesian there is often a lack of interaction between students and teachers. Therefore, it is necessary to apply the discovery learning method in collaboration with the 4C skills so that the learning process is more impactful and enjoyable. This study aims to determine the response of class X-5 students of SMAN 1 Ngamprah in learning exposition text using discovery learning method. The method used is descriptive qualitative method, the instrument used is a questionnaire in the form of a list of statements addressed to class X-5 students of SMAN 1 Ngamprah. The results of the study concluded that the interest of students in class X-5 with the application of discovery learning method in learning exposition texts was around 93.1% interested and 78% agreed that the discovery learning method in learning exposition texts was effective to be applied to students in class X-5 at SMAN 1 Ngamprah.Keywords: discovery learning; exposition texts; SMAN 1 Ngamprah